Istaroxime for Patients with Acute Heart Failure: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Mohamed Abuelazm; Shafaqat Ali; Majd M. AlBarakat; Abdelrahman Mahmoud; Mohammad Tanashat; Husam Abu Suilik; Basel Abdelazeem; James Robert Brašić (Diseases, 2023)
Istaroxime, an intravenous inotropic agent with a dual mechanism—increasing both cardiomyocyte contractility and relaxation—is a novel treatment for acute heart failure (AHF), the leading cause of morbidity and mortality in heart failure. We conducted a systematic review and meta-analysis that synthesized randomized controlled trials (RCTs), which were retrieved by systematically searching PubMed, Web of Science, SCOPUS, and Cochrane until 24 April 2023. We used a fixed-effect or random-effect model—according to heterogeneity—to pool dichotomous data using the risk ratio (RR) and continuous data using the mean difference (MD), with a 95% confidence interval (CI). We included three RCTs with a total of 300 patients. Istaroxime was significantly associated with an increased left ventricular ejection fraction (mL) (MD: 1.06, 95% CI: 0.29, 1.82; p = 0.007), stroke volume index (MD: 3.04, 95% CI: 2.41, 3.67; p = 0.00001), and cardiac index (L/min/m2) (MD: 0.18, 95% CI: 0.11, 025; p = 0.00001). Also, istaroxime was significantly associated with a decreased E/A ratio (MD: −0.39, 95% CI: −0.58, −0.19; p = 0.0001) and pulmonary artery systolic pressure (mmHg) (MD: 2.30, 95% CI: 3.20, 1.40; p = 0.00001). Istaroxime was significantly associated with increased systolic blood pressure (mmHg) (MD: 5.32, 95% CI: 2.28, 8.37; p = 0.0006) and decreased heart rate (bpm) (MD: −3.05, 95% CI: −5.27, −0.82; p = 0.007). Since istaroxime improved hemodynamic and echocardiographic parameters, it constitutes a promising strategy for AHF management. However, the current literature is limited to a small number of RCTs, warranting further large-scale phase III trials before clinical endorsement.